Identification of Short- and Long-Wavelength Emitting Chlorophylls in Cyanobacterial Photosystem I by Plasmon-Enhanced Single-Particle Spectroscopy at Room Temperature - Hatazaki, Soya; Sharma, Dharmendar Kumar; Hirata, Shuzo; Nose, Keiji; Iyoda, Tomokazu; Kölsch, Adrian; Lokstein, Heiko; Vacha, Martin (The journal of physical chemistry letters, 2018)
A peculiarity of cyanobacterial Photosystem I (PSI) is the presence of so-called red chlorophylls absorbing at wavelengths longer than the reaction center P700. The origin and function of these chlorophylls have been debated in literature, but so far no consensus has been reached on either question. Here, we use plasmon-enhanced single-particle fluorescence spectroscopy to elucidate the origin of both short- and long-wavelength emitting species in monomeric PSI from Thermosynechococcus elongatus at room temperature. Polarized fluorescence spectra of single PSI complexes reveal a phase shift in the modulation of the short-wavelength (687 nm) and long-wavelength (717 nm) peaks. Numerical simulations show that this phase shift reflects a spatial angle of 15° between the transition dipole moments of the two forms. Quantum chemical calculations, together with reported X-ray structural and spectroscopic data, were used to assign the chlorophyll a monomer A3 as a candidate for the short-wavelength emitter and the B31-B32 chlorophyll dimer as a candidate for the long-wavelength emitter.
Keywords: fluorescence; Bacteriochlorophylls; Photosystem I Protein Complex; Cyanobacteria; fotosystém I (proteinový komplex); chemické modely; Temperature; Models, Chemical; Fluorescence; sinice; bakteriochlorofyly; kvantová teorie; Spectrometry, Fluorescence; teplota; Quantum Theory; fluorescenční spektrometrie